Pengaruh Pendidikan Multikultural Terhadap Sikap Moderasi Beragama (Studi di MAN 3 Pandeglang Tahun Pelajaran 2023/2024) - Hamdanah, Hamdanah (LPPM STAI La Tansa Mashiro, 2024)
The role of Islamic education is crucial in shaping individual behaviour in today's multicultural society. Multiculturalism as a social theory, emphasises the importance of recognition and appreciation of cultural and religious diversity. The purpose of this study was to determine the effect of multicultural education on the attitude of religious moderation of class XII students of MAN 3 Pandeglang in the 2023/2024 academic year. This research is a quantitative research type with a descriptive approach. Data collection techniques using interviews, documentation studies, and distributing questionnaires. The sample used was 83 students of class XII MAN 3 Pandeglang in the 2023/2024 academic year with a non-probability sampling technique of purposive sampling. Data analysis using descriptive percentage analysis techniques, simple linear regression, and hypothesis testing. The results showed the influence of multicultural education on religious moderation. Based on the results of statistical analysis, the hypothesis test obtained probability (Sig.) 0.000 <0.05 so that the decision H0 is rejected and Ha is accepted. While the coefficient of determination is known to be a value of 0.941. This means that multicultural education has an effect of 94.1% on students' religious moderation. While the remaining 5.9% is influenced by other factors outside the regression equation that are not studied. The suggestion that can be given is that educational institutions must improve the content component of the multicultural education curriculum to lead to a generation that is religiously moderate and teachers as a very important role in fostering student attitudes should always control (supervision) of student religious activities so that the attitude of religious moderation is alive among students. The hope is to be able to produce quality out put, character and can accept and appreciate plurality in order to encourage the growth of unity and integrity. Keywords: Multicultural Education, Attitude of Religious Moderation